Website UI/UX Analysis and Redesign using Usability Testing Methods - Rusdiansyah, Rusdiansyah; Suryanata, Muhammad Fauzan (SAN Scientific, 2024)
Usability has 5 quality dependent variables, namely learnability, efficiency, memorability, error, and satisfaction. With usability testing, it will be assessed whether the user interface and user experience of the website are ready to be implemented or not. One application that can be used is Figma, which is a web-based application. In this study using qualitative research with validation tests, reliability tests, data reduction, data presentation, and drawing conclusions. This qualitative research is supported by the usability testing method as a system development model. This usability testing method is used to find out how easy it is to learn about the website to support the company profile, the ease of use of the website, user/customer satisfaction, and the efficiency of the Dwisetia Garuda Metalindo Sejahtera company website. Usability comes from English, namely usable which refers to the ability to use well. This study tested the validity by calculating the relationship between scores using the SPSS program. In this study, the number of respondents consisting of three categories of respondents namely employees, customers, and the general public was 51 respondents. The data was taken using a questionnaire/questionnaire which was distributed directly via the questionnaire/questionnaire link. Based on the research, it can be concluded from the redesigning of Dwisetia Garuda Metalindo Sejahtera's company website as a support for the company profile. Usability terdapat 5 variabel terikat (dependent) yang berkualitas yaitu learnability, efficiency, memorability, error, dan satisfaction. Dengan usability testing, akan dapat dinilai apakah user interface dan user experience dari website sudah siap untuk diterapkan atau belum. Salah satu aplikasi yang dapat digunakan adalah Figma, yang merupakan aplikasi berbasis web. Dalam penelitian ini menggunakan penelitian kualitatif dengan uji validasi, uji reliabilitas, reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian kualitatif ini di dukung oleh metode usability testing sebagai model pengembangan sistem. Metode usability testing ini digunakan untuk mengetahui sejauh mana kemudahan dalam mempelajari website guna menunjang company profile, kemudahan website untuk digunakan, kepuasan pengguna/pelanggan, dan efisiensi dari website PT Dwisetia Garuda Metalindo Sejahtera. Usability berasal dari Bahasa Inggris yaitu usable yang mengacu pada kemampuan penggunaan yang baik. Penelitian ini melakukan uji validitas dengan menghitung hubungan antar skor menggunakan program SPSS. Dalam penelitian ini, jumlah responden yang terdiri dari tiga (3) kategori responden yaitu karyawan, customer, dan masyarakat umum sebanyak 51 responden. Data tersebut diambil menggunakan angket/kuesioner yang disebar secara langsung melalui link angket/kuesioner tersebut. Berdasarkan dari penelitian, maka dapat disimpulkan dari pembuatan redesain website PT Dwisetia Garuda Metalindo Sejahtera sebagai penunjang company profile.